2022
DOI: 10.1016/j.pmn.2021.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol, Tobacco and Psychotropic Drugs Use Among a Population with Chronic Pain in Southern Spain. A Cross-Sectional Study

Abstract: Background: Substance use seems to be higher among populations with chronic pain. Aim: The aim of this study is to examine the relationship between the quantity of alcohol, tobacco, and psychotropic drugs consumed and chronic pain among women and men. Method: Linear and logistic regression analyses were carried out using data from the 2015-2016 adults' version of the Andalusian Health Survey which is a representative cross-sectional population-based study (n = 6,569 adults aged > 16 years; 50.8% women; 49.2% m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…reported that tobacco use was associated with limited SCS response, with smokers demonstrating higher pain levels at long‐term follow up compared to nonsmokers 56,77 . Importantly, chronic tobacco use has been associated with maladaptive pain behaviors, such as inactivity, reliance on medical management, higher emotional distress, chronic opioid use, pain catastrophizing behavior, psychotropic drugs, and alcohol use in the chronic pain population 78–80 . In addition to tobacco use, a coexisting history of substance abuse, including alcohol has been associated with negative SCS outcomes, and alcohol abstinence has been shown to result in positive outcomes 36,41,42 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…reported that tobacco use was associated with limited SCS response, with smokers demonstrating higher pain levels at long‐term follow up compared to nonsmokers 56,77 . Importantly, chronic tobacco use has been associated with maladaptive pain behaviors, such as inactivity, reliance on medical management, higher emotional distress, chronic opioid use, pain catastrophizing behavior, psychotropic drugs, and alcohol use in the chronic pain population 78–80 . In addition to tobacco use, a coexisting history of substance abuse, including alcohol has been associated with negative SCS outcomes, and alcohol abstinence has been shown to result in positive outcomes 36,41,42 .…”
Section: Discussionmentioning
confidence: 99%
“…56,77 Importantly, chronic tobacco use has been associated with maladaptive pain behaviors, such as inactivity, reliance on medical management, higher emotional distress, chronic opioid use, pain catastrophizing behavior, psychotropic drugs, and alcohol use in the chronic pain population. [78][79][80] In addition to tobacco use, a coexisting history of substance abuse, including alcohol has been associated with negative SCS outcomes, and alcohol abstinence has been shown to result in positive outcomes. 36,41,42 The overall body of evidence seems to favor a negative association of SCS treatment efficacy with tobacco use, however, further studies are needed in the meantime, continued counseling on smoking cessation and patient education of the possible negative impacts of tobacco and polysubstance use is recommended.…”
Section: Alcohol and Tobacco Usementioning
confidence: 99%